Privatization of Rights in the Nineties: The Role Of Political Municipal Education - Reis Silva Júnior, João dos (Education Policy Analysis Archives, 2004)
The goal of this short essay is to study the reforms and political role of the Brazilian process of educational municipalization as well as to analyze some of the changes developed in the space of civil society. To do so, this study analyzes the main documents which oriented and were produced for the reform.